Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1177/0956462413507443
|View full text |Cite
|
Sign up to set email alerts
|

Bringing testing to the people – benefits of mobile unit HIV/syphilis testing in Lima, Peru, 2007–2009

Abstract: Mobile unit (MU) HIV testing is an alternative method of providing healthcare access. We compared demographic and behavioural characteristics, HIV testing history and HIV prevalence between participants seeking testing at a MU vs. fixed clinic (FC) in Lima, Peru. Our analysis included men and transgender women (TW) in Lima aged 18 years old seeking HIV testing at their first visit to a community-based MU or FC from October 2007 to November 2009. HIV testing history, HIV serostatus and behavioural characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 14 publications
0
31
0
2
Order By: Relevance
“…Further revisions to this testing approach could therefore include testing during evenings and weekends, confirming self-reported HIV status using surveillance data, and documenting the numbers of persons who were ineligible due to being HIV positive. In general, the effectiveness of this approach could also be measured by comparing it to other testing schemes such as using a multi-level approach which combines tract-level and individual-level data, venue-based, or clinic-based routine HIV testing [9, 11, 12, 40, 4548], as these approaches may also successfully identify persons at high risk for HIV and have a higher yield of positives.…”
Section: Discussionmentioning
confidence: 99%
“…Further revisions to this testing approach could therefore include testing during evenings and weekends, confirming self-reported HIV status using surveillance data, and documenting the numbers of persons who were ineligible due to being HIV positive. In general, the effectiveness of this approach could also be measured by comparing it to other testing schemes such as using a multi-level approach which combines tract-level and individual-level data, venue-based, or clinic-based routine HIV testing [9, 11, 12, 40, 4548], as these approaches may also successfully identify persons at high risk for HIV and have a higher yield of positives.…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggests that present strategies are working to get individuals most at risk to test at least once, but testing frequency can be improved, and an opt-out model for HIV testing at the time of STI screening, as has been successfully implemented in other low-resource settings, may provide added benefit [24]. Newer innovations which utilize non-traditional approaches to HIV testing, including social media and mobile testing sites, also offer promise [25,26]. As an example, Project Accept - a large multi-country, community-based randomized control trial to promote community-based HTC – showed that with community involvement, HTC in mobile units can increase the frequency of repeat testing [15].…”
Section: Discussionmentioning
confidence: 99%
“…67 There were no data on the proportion of transgender women who engaged in sex work; however, findings from another study in the same city noted that 64% of transgender women report sex work as their main economic activity. 56 The study in Laos assessed the effect of an integrated social marketing approach to HIV prevention in kathoey (a Thai term for transgender women), who were not asked about sex work.…”
Section: Interventions To Prevent Hiv Infectionmentioning
confidence: 98%